Mites (Arachnida: Acarina) Affecting Humans and Steps Taking for the Solution of Problematics - Sarwar, Muhammad (International Journal For Research In Health Sciences And Nursing, 2016)
This article’s goal is to introduce economically efficient, socially acceptable and environmentally benign strategies for controlling allergen producer mites. Mites can significantly impact human’s setups because of annoying and uncomfortable bites which they inflict. Mites have variable life cycles and hosts, and some are public health pests causing irritation of skin due to bites or feeding on host’s skin, fur and feathers; persistent dermatitis in response to invading skin or hair follicles; mite-induced allergies; transmission of pathogenic microbial agents and metazoan parasites; intermediate hosting of parasites, notably tapeworms; and invasion of respiratory passages and ears. There are only a few mite species that cause medical problems for human beings, but it is only itch mite which can be regarded as an important parasite of man, however, other mites may occasionally cause trouble. In particular the harvest mites (Trombicula autumnalis) of family Trombiculidae in their larval stage often bite peoples in late summer and cause intense irritation or a wheal, usually with severe itching and dermatitis, are called chiggers. Mites that cause allergy Dermatophagoides pteronyssinus (House dust mite) and invade skin and cause scabies (scabies mites Sarcoptes scabiei) are important pests of humans, but are not readily controlled through pest control methods. Certain other mites also invade skin or associated hair follicles and dermal glands, and are transmitted from person-to-person through direct contact. Pets, animals and birds that live around peoples surely carry around their own complement of parasitic mites transmissible to humans. Integrated Mite Management (IMM) has the potential to provide long-range and effective control with reduced reliance on pesticides. Community cooperation is required, however, because IMM often depends on structural modifications and sanitation performed by others. Customers must also support ongoing surveillance programs and often should tolerate slow-acting controls and occasional low-level pest sightings. Pest management personnel should educate, encourage, and convince potential customers through a comprehensive public relations effort. Read pesticide’s label carefully and select products appropriate for use indoors or outdoors as needed for mites control.